2002
DOI: 10.1007/s00259-002-0775-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosimetry of radioiodine therapy in benign and malignant thyroid disorders by means of iodine-124 and PET

Abstract: The aim of this study was to evaluate the use of 124I positron emission tomography (PET) to determine the dosimetry of radioiodine therapy in hyperthyroidism and thyroid cancer. Phantom studies to assess the accuracy of PET were performed using an EEC phantom with spheres of different diameters filled with 3-30 MBq of 124I. Patient dosimetry was derived from PET data obtained 1-13 days after simultaneous oral administration of a therapeutic dose of 131I and a diagnostic dose of 124I. The obtained data were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(61 citation statements)
references
References 9 publications
2
55
0
4
Order By: Relevance
“…Using the reference approach (5 PET measurement points from 4 to 96 h), the present study found broadly similar radioiodine kinetics to those observed by other groups investigating 124 I PET dosimetry, albeit we noted wider ranges and higher maximum values than did those groups (3)(4)(5) The clinical course of DTC is often favorable, and standardized radioiodine therapy is well established and frequently successful. In selected patients, an individual therapy needs to be performed at the limits, and prospective dosimetry is required.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using the reference approach (5 PET measurement points from 4 to 96 h), the present study found broadly similar radioiodine kinetics to those observed by other groups investigating 124 I PET dosimetry, albeit we noted wider ranges and higher maximum values than did those groups (3)(4)(5) The clinical course of DTC is often favorable, and standardized radioiodine therapy is well established and frequently successful. In selected patients, an individual therapy needs to be performed at the limits, and prospective dosimetry is required.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the adapted approach used data points from only 2 (24-and 96-h) PET scans and an assumed fixed interception point of 8 h (the median for Table 2 lists the relevant statistical variables, and Figure 3C shows Lin's concordance correlation plots for this adapted approach. Lin's coefficients were identical with those of C 2 (4,24,96). Figure 4C depicts the individual absolute percentage deviation of each lesion with the adapted C 2 (24,96) versus the reference approach.…”
Section: Empiric Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…In such cases, it is necessary to acquire some whole scans starting from 6-7 hours after radio-iodine therapy. (Eschmann et al, 2002) (Sgouros et al, 2004).…”
Section: I Therapy Of Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…PET dosimetry could provide useful routine procedures for radioiodine therapy in advanced differentiated thyroid cancer and might allow safer or more effective radioiodine dose and earlier multimodal interventions than standard empirical protocols. In addition, PET can be used for dosimetric calculation in patients with Graves' disease and autonomously functioning nodule (11).…”
mentioning
confidence: 99%